SAT0355 Real World Risk of Infusion Reactions with Pegloticase Treatment: Findings from Post-Approval us Safety Data. (23rd January 2014) - Malamet, R.; Howson, T.; Yeo, A.; Bahrt, K.
Abstract : Background: Pegloticase was recently approved in the EU for severe debilitating chronic tophaceous gout in patients refractory or with intolerance to xanthine oxidase inhibitors. The pegloticase development program included 2 replicate randomized, placebo-controlled trials (RCTs; 6 months; N=212) 1 followed by an open-label extension study. 2 Patients were considered plasma uric acid (UA) "responders" if they met the primary end point of UA <6 mg/dL (360μmol/L) for 80% of time during months 3 and 6, and 42% of patients met this end point (vs 0% with placebo; P <0.001). Post-hoc analyses from the RCTs revealed that UA nonresponse was associated with high titer antibodies against pegloticase resulting in increased drug clearance and risk for infusion reactions (IRs). Pegloticase treatment recommendations thus include that UA be monitored prior to infusions and discontinuation considered if serum UA exceeds 6 mg/dL (particularly with 2 consecutive levels >6 mg/dL). During the RCTs, IRs were reported for 26% (56/212) of patients (including 4 cases retrospectively characterized as anaphylaxis based on published criteria 1 ). This IR rate was attained before the relationship between UA levels, antibody development and IR risk was understood, as investigators were blinded to UA levels. 2 Objectives: To assess infusion-related reactions in patients treated with pegloticase in the US from post-approval safety surveillance data (to be updated with 2013 data). Methods: IRs were defined as adverse events (AEs) that occurred during or within 2 hours following the end of study drug infusion that could not be reasonably attributed to another cause. The incidence of IRs was drawn from voluntary AE reporting. An estimate of the total number of infusions given in the same period was derived from the number of vials sold during that period compared with the number administered to a defined number of patients during the 6 months of randomized trial participation. Results: The table displays IR rates per total infusions during the randomized trials and reported during the 2-year post-approval period. The relative risk reduction for IRs during post-approval compared with clinical trial data was 68.7% (95% CI: 49.8 to 80.5). Post-approval IRs occurred in less than 1 of 100 infusions. Conclusions: The rate of IRs appeared to decrease during the post-approval period (in the US) compared with the randomized trial period. While there are limitations inherent in determining AEs from voluntary reports and in estimating numbers of patients receiving infusions, we will continue to assess whether IR risk is mitigated by adherence to recommended guidelines. These guidelines include monitoring UA levels prior to each infusion and discontinuing therapy when serum UA rises to >6mg/dL (particularly with 2 consecutive levels >6mg/dL). References: Sampson et al. Ann Emerg Med 2006 Sundy et al. JAMA 2011 Disclosure of Interest: R. Malamet Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., T. Howson Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., A. Yeo Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., K. Bahrt Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc.